Upaya Peningkatan Minat Belajar di Era New Normal Pada Anak-Anak Warga Dusun II Desa Tumpatan - Neni Triastuti; Fahmi Sulaiman (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The problem of online learning is one of the problems felt by all children and adults. As in the learning era in the midst of a pandemic, learning has not yet obtained maximum results and is even lagging behind other countries. The purpose of this community service is so that school-age children do not feel bored because of online learning and have a high interest in learning in the future. Then knowledge and understanding are given to the target regarding the procedures for building interest in learning, so that it is hoped that they can learn according to government regulations. The target achieved in this service is to increase interest in learning and will increase knowledge in being a student in the midst of the Covid 19 pandemic. The method used is to provide socialization on procedures for building interest in learning to redefine knowledge that was left behind due to the pandemic. The resulting learning process to the government and provide knowledge, understanding and skills of learners. The lecture method and visits from participants as well as evaluating explanations about increasing interest in learning using learning media will provide a more real assessment of the target for the success of this activity. It is hoped that the target will participate in the socialization seriously and is targeted to produce knowledge and skills in general knowledge both online so that it can provide even better benefits in increasing knowledge.